Wernekink Commissure Syndrome Secondary to Bilateral Caudal Paramedian Midbrain Infarction Presenting with a Unique “Heart or V” Appearance Sign: Case Report and Review of the Literature - Zhou, Chenguang; He, Yuanhong; Chao, Zhiwen; Zhu, Yinghui; Wang, Peng; Wang, Xingping; Liu, Shanshan; Han, Wei; Wang, Jianping (Frontiers in Neurology, 2017)
Wernekink Commissure Syndrome secondary to caudal paramedian midbrain infarction (CPMI) is a rare midbrain syndrome involving the decussation of the superior cerebellar peduncle in the caudal paramedian midbrain tegmentum. The central characteristics are constant bilateral cerebellar dysfunction, variable eye-movement disorders and rare delayed palatal myoclonus. Following is a description of the case of a 60-year-old man who presented with dizziness, slurred speech and difficulty walking. Neurological examination revealed bilateral cerebellar dysfunction and bilateral internuclear ophthalmoplegia (bilateral INO). Serial magnetic resonance imaging (MRI) revealed a lesion in the caudal paramedian midbrain with a “heart-shaped” sign on fluid-attenuation inversion recovery images and a “V-shaped” appearance on diffusion-weighted imaging (DWI). An acute CPMI with a “heart or V” appearance sign was diagnosed. Upon follow-up evaluation three months later, a palatal tremor accompanied by involuntary head tremor was discovered. Hypertrophy and increased signal of the bilateral inferior olivary nucleus, compatible with hypertrophy olivary degeneration (HOD) were revealed during a subsequent MRI study.